«Фундамент» Києва - Степанюк, Л.М.; Приходько, В.Л.; Курило, С.І.; Довбуш, Т.І.; Котвіцька, І.М. (Вісник НАН України, 2017)
Київ розташований у межах східного схилу Українського щита. Кристалічний фундамент представлений метаморфічними породами росинсько-тікицької серії та гранітоїдами, що розвиваються по них, і перекритий
фанерозойським чохлом, потужність якого зростає із заходу на схід і варіює від десятків до сотень метрів. Породи кристалічного фундаменту території м. Київ для дослідження було піднято на денну поверхню нечисленними свердловинами, однією з яких є Новобіличанська свердловина № 1 глибиною 1927 м. За матеріалами буріння, кристалічний фундамент
залягає на глибині 290 м. Породи фундаменту представлено переважно
тіньовими мігматитами гранодіоритового складу з малопотужними лінзоподібними включеннями амфібол-біотитових гнейсів. За результатами уран-свинцевого ізотопного датування кристалів цирконів без видимих
реліктових ядер, вік гранодіориту становить 2059 ± 12 млн років. З’ясовано, що гранодіорити сформувалися по палеопротерозойському коровому субстрату (εNd = −2,1; ⁸⁷Sr/⁸⁶Sr = 0,70501 ± 6), речовина якого відділилася
від деплетованої мантії не раніше 2,42 млн років тому, тобто в палеопротерозої. Kyiv is located within the Eastern slope of the Ukrainian Shield. The crystalline basement is represented by metamorphic
rocks of Ros’-Tikych series and granitoids. The basement is closed off by Phanerozoic cover, the thickness of which
increases from West to East and varies from tens to hundreds of meters. Rocks of the crystalline basement of Kyiv were
raised for the study to the surface through a few boreholes, one of which is Novobelitska 1 with a depth of 1927 m.
According to drilling materials the crystalline basement lies at 290 m. Basement rocks are represented mainly by shadow
migmatite of granodiorite composition with small lenticular inclusions of amphibole-biotite gneiss. The main goal of the
research is to determine the time and origin of granodiorite melts. Zircon was dated by uranium-lead method, isotope
composition of strontium was studied in apatite and Sm-Nd isotope systems in the granodiorite. The sample from the
borehole was tested at the interval of 488-504 m. The age of the granodiorite in 2059±12 million years was determined
based on the results of uranium-lead isotopic dating of the zircon crystals with no visible relict cores. The Sm-Nd isotopic
studies of bulk sample of the granodiorite and the isotopic composition of strontium in accessory apatite found that the
granodiorites formed by Paleoproterozoic crustal substrate (εNd = –2.1; ⁸⁷Sr/⁸⁶Sr = 0.70501 ± 6), the substance of which
was separated from depleted mantle no earlier than 2.42 million years ago in Paleoproterozoic.